TGFβ depletion does neither modulate acute E. coli-induced inflammatory immune responses nor impair the protective effect by chronic filarial infection - Buerfent, Benedikt C.; Ajendra, Jesuthas; Stamminger, Wiebke; Gondorf, Fabian; Hoerauf, Achim; Hübner, Marc P. (GMS Infectious Diseases, 2019)
TGFβ is an anti-inflammatory molecule that suppresses pro-inflammatory immune responses. Previously, we demonstrated that chronic filarial infection has a beneficial impact on -induced sepsis. In the present study, we investigated whether this protective effect is dependent on TGFβ signaling and whether depletion of TGFβ before challenge alters the early course of sepsis . depletion of TGFβ before challenge did not alter levels of pro-inflammatory cytokines/chemokines and did neither increase the bacterial burden nor worsen -induced hypothermia six hours post challenge. Similarly, in the co-infection model, despite TGFβ depletion, mice infected with the filarial nematode exhibited milder -induced hypothermia, reduced bacterial load and pro-inflammatory immune responses. Thus, we conclude that TGFβ is not essentially modulating the initial pro-inflammatory phase during sepsis and that the protective effect of a chronic filarial infection against sepsis is independent of TGFβ signaling.